The Effect of Speed Exercises on Kinetic Response and Block Skill in Volleyball - Labeeb Zouyan Mosiseek (Journal of Global Pharma Technology, 2018)
Sport training, according to the Recurring training, is considered one of the important fundamentals that all rapid sports depend on. Volleyball is one of these important sports. Rising up the level of skills requires major training effort that can be known through the physical and functional competence. Volleyball depends fully on the system of the anaerobic energy Through at Recurring training due to the nature of this sport that requires quick response for the players' limbs so as to face some sudden difficult balls. That system does not need oxygen foe a very short period of time. The physiological variables give a general assessment of the efficiency and capacity of the muscles to work in the absence of oxygen. This requires coaches and players to be aware of the functions of the various parts of the body. Thus, they determine the components of training load to improve the level of sports. Areas of Research 20 players was divided into two groups the first experimental and the second control group. Conclusions it The recurring training, lead to a positive change in the proportion of the rapid interaction activity in muscle and lead to raising up the level of the kinetic response. Codifying the elements of training with the high interval training style has a significance to improve the physical and physiological competence. Special Speed exercises used in the training curriculum effectively contributed in improving the performance for Physical performance and skill of volleyball player.Keywords: Speed exercises, Kinetic Response, Block, Skill and Volleyball.